Perbedaan Generasional dalam Memaknai Praktik Periklanan Digital oleh Influencer di Media Sosial - Syaifa Tania (Universitas Serang Raya, 2022)
The Y and Z generation is currently the two generations who lives side by side and considered possess higher characteristics compared to the older generations. In terms of technology, although both are considered as digital natives, but they shared different socio-technological context. The Y generation experienced technological adaptation process of the transition of analogue to digital technology. Hence, the Z generation do not share the same experiences. In terms of marketing communication, this condition affects their way of responding digital advertising practice, especially done by the influencer. This research is aimed to explore generational gap between two generations in interpreting the practice of digital advertising shared by social media influencer by using case study method. The result shows existing differences related to the type of the preferred media and their construction of ideal figures of the social media influencers. It shows that the considered similar characteristics between two generations does not entirely correct. The difference lies in their perspective of influencer realness in terms of their personality and persuasive information. Understanding the difference perspectives between two generations leads to the consideration of the future mutigenerational marketing communication approach.